Towards a framework for a collaborative support model to assist infection prevention and control programmes in low- and middle-income countries: a scoping review - Adams, Festus; Zimmerman, Peta-Anne; Sparke, Vanessa L.; Mason, Matt (International Journal of Infection Control, 2023)
Background: Infection prevention and control (IPC) in low- and middle-income countries (LMIC) is reported to be poorly supported because of limits in financial, human and physical resources and competing priorities in health budgets. As a result, there is often a role for external agencies to assist in strengthening IPC. While there are reports of how these partnerships have been put into practice, there are no reported frameworks or guidance documents to support the development of such relationships. Aim: The aim of this study is to identify the core elements of a collaborative support framework to assist LMIC in strengthening IPC. Methods: To achieve this, a systematic scoping review of available literature was conducted based on the guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA 2020). The databases MEDLINE, CINAHL, Embase and Scopus were utilised. The search strategy included different combinations of Medical Subject Heading (MeSH) terms, Emtree and keywords that are relevant to IPC collaboration in LMIC. Literature was limited to that published between 2005 and 2020 in the English language only. Results: Six core elements of comprehensive IPC collaborative support were identified with five IPC programme areas as minimum requirements, namely: 1) Collaborative Projects, 2) Policies and Procedures, 3) Training and Professional Development, 4) Surveillance Systems and 5) Assessment and Feedback. The last element, 6) Partnerships, was identified as an enabling factor. Conclusion: These six core elements should be considered when building a collaborative support model to assist IPC in LMIC.